Instilling the System of Values in Preschool Children in the Cultural and Educational Space - Zdanevych, Larysa; Syrova, Yuliia; Kolosova, Svitlana; Pyvovarenko, Maryna; Kurhannikova, Olha (My University, 2020)
The research was conducted in order to establish the most effective ways of forming a general system of values in preschool children. Emphasis is placed on the unification of methods of moral and ethical education of 3-6-year-old children, and the development of educational model that would contribute to the child's optimal understanding of basic moral principles of mankind. In this regard, the experiment was conducted on a research group consisting of 710 children aged 3-6, which also included 192 parents and 50 teachers. In addition, 52 books of short stories and fairy tales were selected for the study, on the basis of which the main value preferences and orientations of preschool children were determined. According to the preferences of children, parents or teachers, certain texts were selected from the defined 52 stories and fairy tales for detailed textual analysis for children to differentiate the most common moral values, the range of which was also clearly defined and limited to 20 concepts. As a result of the study, children often paid attention to the values of happiness, peace, cooperativeness and honesty. Beauty, kindness, friendship and purity also attracted significant attention of preschoolers. However, for example, avail, humility, tolerance, hospitality and respect were rarely emphasized by children. Patriotism as a value has generally gone unnoticed. The results of the study might be used as auxiliary material for teachers in the preparation and selection of teaching materials in terms of value orientations in preschool children, as well as in the parents’ choice of children's literature that would clearly reflect the inner world of the child and be understood in terms of axiological component
Instilling the System of Values in Preschool Children in the Cultural and Educational Space / Larysa V. Zdanevych, Yuliia V. Syrova, Svitlana V. Kolosova, Maryna S. Pyvovarenko, Olha O. Kurhannikova // Universal Journal of Educational Research. – 2020. – № 8 (11B). – С. 5991–5999.
Keywords: діти дошкільного віку, моральні цінності, світогляд, дошкільна освіта, розповіді, казки; Preschool Children, Moral Values, Worldview, Preschool Education, Stories, Fairy Tales; дети дошкольного возраста, моральные качества, мировозрение, дошкольное образование, рассказы, сказки